Preservation and Tissue Handling Technique on Iatrogenic Dural Tear with Herniated Nerve Root at Cauda Equina Level - Ahmad Jabir Rahyussalim; Yoshi Pratama Djaja; Ifran Saleh; Ahmad Yanuar Safri; Tri Kurniawati (Case Reports in Orthopedics)
Iatrogenic or incidental dural tear is a relatively common complication in lumbar decompression surgery. Although mostly there are no changes that occurred in long-term result following an incidental durotomy, the sequelae are not always benign especially when the herniated nerve root is involved. Preservation and tissue handling is paramount in order to prevent further injury. Two cases of dural tear with herniated nerve root complicating the lumbar decompression surgery are presented. Direct watertight repair was performed using the preservation and tissue handling concept. Assessing the relative size between the dural tear and the root mass is the key in determining whether enlargement of tear is needed. Whenever feasible, the tear will not be enlarged. Opening the vent by using a suture anchor and manually repositioning the nerve root with a fine instrument is the key for an atraumatic handling of the herniated nerve root. Clinical and neurophysiology examination was performed postoperatively and no further neurologic deficit occurred despite the iatrogenic injury. Although some debate on a few intraoperative and postoperative details still persists, tissue handling and preservation concept should be applied in all cases.